(untitled) (Development Engineering Conferences Center Articles Database, 2026)
Cuminum cyminum L. (green cumin) is an aromatic medicinal herb widely recognized for its pharmacological and therapeutic properties, including antimicrobial, antioxidant, and digestive activities. The present investigation aimed to extract the essential oil from C. cyminum seeds by hydrodistillation method, formulate a physically stable nanoemulsion using high‑speed homogenization, identify and quantify the volatile components of the essential oil, and assess the antimicrobial efficacy of the obtained nanoemulsion. The chemical profile of the essential oil, analyzed by gas chromatography–mass spectrometry (GC–MS), revealed that cuminaldehyde, γ‑terpinene, and p‑cymene were the predominant constituents. The formulated nanoemulsion exhibited high physical stability with a mean droplet diameter of approximately 8.1 nm and a narrow size distribution. Antimicrobial assays demonstrated that the cumin essential oil nanoemulsion exhibited strong inhibitory effects against a broad spectrum of foodborne bacterial pathogens. These findings suggest that cumin essential oil nanoemulsion could serve as a promising natural antimicrobial agent for potential applications in food preservation and safety enhancement.